(untitled) (Canadian Medical Education Journal, 2019)
Motivation is a major indicator of students’ learning behaviors. Therefore, researchers require consistent and valid instruments to assess students’ motivation. Consequently, motivation has been an important topic in medical education research for the last decade. The present study evaluated the construct and predictive validities of the French version of the Strength of Motivation for Medical School-Revised questionnaire (SMMS-R-FR). Our sample comprised 372 students at three French-speaking medical schools, who filled in the SMMS-R-FR and the Revised two-factor Study Process Questionnaire (R2-SPQ). Results confirmed the three-factor structure of the original SMMS-R questionnaire. Reliabilities were good for the Total Strength of Motivation scale, moderate for the Willingness to Sacrifice and Readiness to Start subscales, and poor (but still acceptable) for the Persistence subscale. Both Total Strength of Motivation and Readiness to Start positively predicted a deep learning approach and negatively predicted a surface learning approach, while Willingness to Sacrifice positively predicted a deep learning approach and Persistence negatively predicted a surface learning approach. Our results both support the SMMS-R-FR’s suitability as a tool for measuring motivation in medical students, and suggest that it could be used to guide the development of educational interventions to strengthen motivation.